Cost effectiveness of clinically appropriate decisions on alternative treatments for angina pectoris: prospective observational study. Issue 7594 (5th March 2007) - Griffin, S C; Barber, J A; Manca, A; Sculpher, M J; Thompson, S G; Buxton, M J; Hemingway, H
Abstract : Objective To assess whether revascularisation that is considered to be clinically appropriate is also cost effective. Design Prospective observational study comparing cost effectiveness of coronary artery bypass grafting, percutaneous coronary intervention, or medical management within groups of patients rated as appropriate for revascularisation. Setting Three tertiary care centres in London. Participants Consecutive, unselected patients rated as clinically appropriate (using a nine member Delphi panel) to receive coronary artery bypass grafting only (n=815); percutaneous coronary intervention only (n=385); or both revascularisation procedures (n=520). Main outcome measure Cost per quality adjusted life year gained over six year follow-up, calculated with a National Health Service cost perspective and discounted at 3.5%/year. Results Coronary artery bypass grafting cost £22 000 (€33 000; 43 000) per quality adjusted life year gained compared with percutaneous coronary intervention among patients appropriate for coronary artery bypass grafting only (59% probability of being cost effective at a cost effectiveness threshold of £30 000 per quality adjusted life year) and £19 000 per quality adjusted life year gained compared with medical management among those appropriate for both types of revascularisation (probability of being cost effective 63%). In none of the three appropriateness groups was percutaneous coronary intervention cost effective at a threshold of £30 000 per quality adjusted life year. Among patients rated appropriate for percutaneous coronary intervention only, the cost per quality adjusted life year gained for percutaneous coronary intervention compared with medical management was £47 000, exceeding usual cost effectiveness thresholds; in these patients, medical management was most likely to be cost effective (probability 54%). Conclusions Among patients judged clinically appropriate for coronary revascularisation, coronary artery bypass grafting seemed cost effective but percutaneous coronary intervention did not. Cost effectiveness analysis based on observational data suggests that the clinical benefit of percutaneous coronary intervention may not be sufficient to justify its cost.